Three-dimensional 31P magnetic resonance spectroscopic imaging of regional high-energy phosphate metabolism in injured rat heart. - von Kienlin, M; Rösch, C; Le Fur, Y; Behr, W; Roder, F; Haase, A; Horn, M; Illing, B; Hu, K; Ertl, G; Neubauer, S (1998)
The purpose of this study was to measure the spatially varying 31P MR signals in global and regional ischemic injury in the isolated, perfused rat heart. Chronic myocardial infarcts were induced by occluding the left anterior descending coronary artery eight weeks before the MR examination. The effects of acute global low-flow ischemia were observed by reducing the perfusate flow. Chemical shift imaging (CSI) with three spatial dimensions was used to obtain 31P spectra in 54-microl voxels. Multislice 1H imaging with magnetization transfer contrast enhancement provided anatomical information. In normal hearts (n = 8), a homogeneous distribution of high-energy phosphate metabolites (HEP) was found. In chronic myocardial infarction (n = 6), scar tissue contained negligible amounts of HEP, but their distribution in residual myocardium was uniform. The size of the infarcted area could be measured from the metabolic images; the correlation of infarct sizes determined by histology and 31P MR CSI was excellent (P < 0.006). In global low-flow ischemia (n = 8), changes of HEP showed substantial regional heterogeneity. Three-dimensional 31P MR CSI should yield new insights into the regionally distinct metabolic consequences of various forms of myocardial injury.